Pendidikan Kesehatan tentang Kesehatan Reproduksi pada Remaja di SDK Untung Suropati 2 Sidoarjo - Widianingtyas, Sisilia Indriasari; Yuliana, Widayani; Wiguna, Yunita (Jurnal Abdimas Kesehatan (JAK), 2025)
Reproductive healthy is a state of health related to problems with the organs of reproduction, which begins in adolescence, marked by the onset of menstruation in girls or wet dreams in boys. Sex education for adolescents provides knowledge about sexual aspects and develops constructive attitudes for adolescents in dealing with sexual problems that occur early. Taboo views surrounding information about reproductive healthy within families result in the ineffective dissemination of such information. Therefore, comprehensive and targeted reproductive health education interventions are needed for adolescents to help them understand bodily changes, reproductive roles, as well as risks and prevention methods. The educational session was conducted on Friday, October 4, 2024. Participants in the educational activity were all students in grades 5 and 6 at SDK Untung Suropati 2 Sidoarjo. The material was presented in the form of a PowerPoint presentation designed to be as engaging as possible, making it easier for participants to understand the content. The evaluation results showed that 97% of participants were able to understand physical changes during puberty, the risks of sexually transmitted diseases (STDs), how to maintain reproductive organ hygiene and the risks of infection, some incorrect information about sexuality, hormonal changes and emotional development during puberty, and the importance of reproductive organ hygiene.